Financial Dependence, Formal Credit and Firm Informality: Evidence from Peruvian Household Data - Eduardo Morón; Edgar Salgado; Cristhian Seminario (Inter-American Development Bank (IDB), 2012)
This paper examines the link between financial deepening and formalization in Peru. Using data from the National Household Survey, Bloomberg and the Central Bank of Peru Central Bank, the Cata~o, Pages, and Rosales (2009) model is implemented at activity level (2-digits ISIC), and the Rajan and Zingales (1998) approach of sectors dependence on external funds is followed. The sample is divided into three firm size categories, and two formality measures are assessed. Using the accounting books specification, robust results are obtained, supporting a significant and positive effect of credit growth on formalization only for the self-employment firms category. Alternatively, using the pension enrollment specification, the channel is found positively significant only for firms with more than 10 workers; there is a smaller effect for firms with 2-10 workers. There is also a significant between effect, explaining the transition from small firms to larger firms due to greater credit availability.
Keywords: E26; G21; O16; O4; 330